An evaluation of using playful and non-playful tasks when teaching research methods in adult higher education. Issue 5 (3rd September 2018) - King, Pete
ABSTRACT: The use of playfulness in higher education has been considered sparsely when compared to other areas of education, such as primary schools. This paper is an evaluation, and a piece of reflective practice, of teaching a research module to postgraduate students using a combination of playful and non-playful tasks. The evaluation indicates that when initially participating in a playful task, students do not make the links with how it relates to research when compared to non-playful tasks. However, once the playful task is complete, students can relate the task to the research process. For both playful and non-playful tasks, there was a difference in how much students enjoyed participating in them. This could relate to whether the tasks were an individual or group task. There was also a difference in how helpful the playful tasks were, compared with the non-playful tasks, for completing the assignment. This evaluation considers the use of playfulness when teaching not only research, but any subject within higher education.